Enantioselective Allylation of β‐Haloacrylaldehydes: Formal Total Syntheses of Pteroenone and Antillatoxin. Issue 12 (6th April 2016) - Koukal, Petr; Ulč, Jan; Nečas, David; Kotora, Martin
Abstract: A comparative study of the catalytic allylations and crotylations of ( E )‐ and ( Z )‐haloacrylaldehydes by Lewis bases (chiral N, N′ ‐dioxides) and Brønsted acids (chiral phosphoric acids) was undertaken. The reactions proceeded with high enantio‐ and diastereoselectivities with slightly better asymmetric induction observed in the case of N, N′ ‐dioxide catalysis. The formed enantioenriched chiral unsaturated haloalcohols could be considered general building blocks, as they could be used in the syntheses of more complex natural products possessing substituted 1, 3‐diene fragments. This was exemplified by the formal total syntheses of pteronenone and antillatoxin. Abstract : A comparative study of allylations and crotylations of ( E )‐ and ( Z ) ‐ haloacrylaldehydes is undertaken under Lewis base and Brønsted acid catalysis. The reactions proceed in both cases with high enantio‐ and diastereoselectivities. The formed chiral unsaturated haloalcohols can be considered as general building blocks, as exemplified by the formal total syntheses of pteronenone and antillatoxin; HBPin = pinacolborane.